Pemberdayaan Masyarakat Berbasis Potensi Desa melalui Digitalisasi di Desa Sungai Pinang - Amin, Muhammad; Guswanti, Nelia; Fadhilatul Hikmah, Wahyu; Mohd. Fauzi, Irfan; Nikmah, Nikmah (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
This study was motivated by the condition of Sungai Pinang Village, Kampar Regency, which possesses considerable agricultural, fisheries, and cultural potential, yet remains underutilized due to limited access and low levels of digital literacy. The purpose of this research was to formulate a community empowerment model based on local village potential through digitalization to enhance community capacity and expand market access. The method applied was community service with a participatory approach using Asset-Based Community Development (ABCD). The stages of implementation included asset and problem mapping, socialization, digital literacy training, formation of village digital cadres, development of digital platforms, program implementation, mentoring, and participatory evaluation. The subjects of this study were community members and village officials, while data were collected through surveys, interviews, focus group discussions, and direct observation. The findings revealed a significant increase in digital literacy, content creation skills, and the use of online marketplaces. The level of community understanding of smartphone usage increased from 45% to 85%, content creation skills improved from 15% to 70%, and the use of digital platforms for business grew from 25% to 78%. These results demonstrate that digitalization not only enhances technical skills but also shifts community mindsets to become more adaptive to technology. In conclusion, village digitalization based on local potential proved effective as a sustainable and inclusive empowerment strategy that fosters community welfare. The implication of this research suggests the need for stronger digital infrastructure and continuous mentoring to ensure the program’s replication in other villages